Field notes contributed by Gladys Black, winter 1978-1979 - Black, Gladyset al (1978)
Winter report of birds found at Red Rock as well as statewide bird sightings contributed by Gladys Black. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed